Upaya Meningkatkan Daya Saing melalui Penguatan Kelembagaan BUMDesa - Sakti, Rachmad Kresna; Bintoro, Nugroho Suryo; Kadafi, Muhammad Amin; Setyanti, Axellina Muara (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2023)
In the year 2021, the launch of the Cultural Village was conducted in Kendalrejo Village because Kendalrejo is among the seven villages in Blitar Regency that has been bestowed with the title of Empowered Village. However, the current development of the Village-Owned Enterprises (BUMDesa) has not experienced a significant improvement, triggered by various factors. The understanding regarding the management of BUMDesa remains uneven, sustainability in the supply of goods, market expansion through increased production hindered by capital constraints that still become challenges for BUMDesa Sumber Rejeki. The Community Service Team observed institutional issues within BUMDesa Sumber Rejeki in Kendalrejo Village, Srengat Sub-district, Blitar Regency. This initiative aims to enhance the managerial capacity of BUMDesa. Employing the approach of sharing, exploring, analysis, and drafting methods, a comprehensive understanding among all stakeholders, especially village officials, regarding the importance of BUMDesa development and strengthening was achieved. This encompassed a profound comprehension of the potentials, obstacles, and development strategies of BUMDesa Sumber Rejeki. The resulting recommendation, denoted as ‘HARMONI DESA' is proposed to fortify the institutional framework of BUMDesa and enhance the welfare of the community.